2020
DOI: 10.30598/ajitt.2019.7.2.69-76
|View full text |Cite
|
Sign up to set email alerts
|

KUALITAS NUTRISI AMPAS SAGU HASIL FERMENTASI JAMUR TIRAM PUTIH (Pleurotus ostreatus) DENGAN WAKTU PANEN YANG BERBEDA

Abstract: Improving local feedstuff which is abundantly available in Maluku Province suh as sago (Metroxylon rumphii) by-product to be a nutritional feedstuff for live is an innovative way to address the scarcity of nutritious feed for livestock in Maluku. The purpose of this research was arranged into a complete randomized design with four treatments: control (no fermentation), before harvest (after full mycelium), the first harvest, and the second harvest. Each treatment was replicated triple. Least square test was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
2
0
4
Order By: Relevance
“…The study conducted by [27] found that the lignin content in tofu dregs was relatively the same, IOP Publishing doi:10.1088/1755-1315/1286/1/012021 7 namely 5,17% (0 day incubation) and 5,13% (70-80 day incubation) using Pleorotus ostreatus.…”
Section: The Effect Of Type Of Fungi and Dosage Used On Larvae Black ...mentioning
confidence: 98%
“…The study conducted by [27] found that the lignin content in tofu dregs was relatively the same, IOP Publishing doi:10.1088/1755-1315/1286/1/012021 7 namely 5,17% (0 day incubation) and 5,13% (70-80 day incubation) using Pleorotus ostreatus.…”
Section: The Effect Of Type Of Fungi and Dosage Used On Larvae Black ...mentioning
confidence: 98%
“…Degradasi ADF ada hubungannya dengan kandungan NDF dan degradasi terhadap hemiselulosa, karena ADF merupakan selisih dari NDF dan hemiselulosa. Pluerotus oestreatus mampu merombak ikatan lignoselulosa yang merupakan komponen ADF seperti yang dilaporkan Jafari et al, (2007), dan Sangadji et al (2008) bahwa semakin lama fermentasi maka semakin berkurang 48,66% (lama inkubasi 0 hari), 40,01% (lama inkubasi 70-80 hari) kadar ADF pada ampas sagu yang difermentasi dengan P. oestreatus. Hasil penelitian ini selaras dengan penelitian Manu et al (2015) yang juga mendapatkan hasil yang sama di mana kandungan komponen serat limbah kelapa muda akibat fermentasi dengan Pleurotus ostreatus yang semakin menurun dengan meningkatnya lama inkubasi.…”
Section: Kandungan Adf Sabut Kelapa Tuaunclassified
“…Hasil penelitian Sangadji et al (2008) juga melaporkan bahwa kadar lignin ampas sagu relatif sama yaitu 5,17% (lama inkubasi 0 hari) dan 5,13% (lama inkubasi 70-80 hari) yang difermentasi dengan P. oestreatus. Hasil tersebut mengindikasikan bahwa lama fermentasi telah memberikan pengaruh yang relatif sama terhadap perombakan komponen sel utama terutama lignin.…”
Section: Kandungan Lignin Sabut Kelapa Tuaunclassified
See 1 more Smart Citation
“…Utilization of repu is still very limited and sometimes discarded so that it can become waste that causes environmental pollution. The repu content component of the proximate analysis results has a crude protein content of 2.1%; fat 1.8%; crude fiber 20.3%; gray 4.6%; cellulose 36.3%; hemicellulose 14.6%; lignin 9.7%; and 3.3% silica [3].…”
Section: Introductionmentioning
confidence: 99%